Manifestaciones orales en pacientes con anorexia mediante revisiones bibliográficas - Roblez Vargas, Jennifer Paulina (2023)
The condition of anorexia nervosa represents one of the most prevalent and severe psychiatric eating disorders. A robust interaction exists between oral health and mental health. Individuals with mental illnesses, particularly severe mental illnesses, face an elevated risk of oral health issues due to inadequate nutrition and oral hygiene. Consequently, this study aimed to identify the most frequent oral manifestations in patients with anorexia through a literature review incorporating specific inclusion and exclusion criteria. The obtained results revealed that the most prevalent oral manifestation is periodontal diseases, accounting for 16.8%, followed by dental erosion at 15.6%, and dental caries and mucosal alterations at 14.4%. The average age commonly associated with this pathology falls within the range of 10 to 19 years, with a prevalence of 92.85% reported in females. In conclusion, a higher prevalence of periodontal alterations, followed by dental hard tissues, such as erosion, caries, and abrasion, is observed in adolescent patients, predominantly females, as a consequence of this disorder